Comparative multiomics analyses reveal the breed effect on the colonic host–microbe interactions in pig - Liang Huang; Shiqi Luo; Shuqi Liu; Mingliang Jin; Yizhen Wang; Xin Zong (iMetaOmics)
Abstract Dysregulation of the gut microbiota often leads to immune‐related disorders, indigestion, or diarrhea. Here, Jiaxing Black (JXB) pig, a local Chinese pig breed known for its great tolerance and digestibility of nutrients, was employed for a metagenomic and transcriptomic integrative analysis to reveal the gut microbiota‐genes and gut microbiota‐pathway interactions. A total of 452 differentially expressed genes, and 174 phyla were found between the JXB and the Duroc × Landrace × Yorkshire (DLY) pigs. Detailed analysis revealed that the differences in colon gene expression signatures between the JXB and DLY are mainly enriched in metabolic and inflammatory responses, with Lactobacillus and Lachnospiraceae enriched in DLY and JXB, respectively. Notably, Pacebacteria, Streptophyta, and Aerophobetes were found to participate in the PI3K‐Akt mediated immune response in both pig breeds; however, they only accelerated the metabolism in the intestines of JXB pigs. Moreover, the host could regulate microbe metabolism and immune response by Ig‐like domain‐containing protein and ITIH2, PAEP, and TDRD9, respectively. Taken together, our results revealed both common and breed‐specific regulations of host genes by gut microbiota in two pig breeds.